Finite element stress and vibration analysis of ball bearings - Cheong, Meng Wei (Nanyang Technological University, 2022)
Ball bearings are widely used in rotary machineries. Bearings are usually subjected to loads from the shaft during operation. In this report, an attempt is made to carry out finite element analysis of a ball bearing subjected to radial loads from the shaft. A 2D sectional view of the ball bearing together with a shaft were modelled. The force and stress distributions in the ball elements are then analysed. ANSYS Mechanical APDL is used for the finite element analysis. Load-displacement characteristics in the ball elements are evaluated at varying displacement of the shaft. The natural frequencies and mode shapes of the ball bearing are also analysed. The load and stress analysis shows that majority of the load is shared by the ball elements in the upper half of the ball bearing when the radial load is upwards. The balls in the lower half do not carry any load. Observations from the von Mises stress analysis shows that the highest stress regions occur at the point contacts between the ball element and raceways as one would expect.